2017
DOI: 10.2147/copd.s143656
|View full text |Cite
|
Sign up to set email alerts
|

Scientific rationale for the possible inhaled corticosteroid intraclass difference in the risk of pneumonia in COPD

Abstract: Inhaled corticosteroids (ICSs) treatment combined with long-acting β2-adrenoceptor agonists (LABAs) reduces the risk of exacerbations in COPD, but the use of ICSs is associated with increased incidence of pneumonia. There are indications that this association is stronger for fluticasone propionate than for budesonide. We have examined systematic reviews assessing the risk of pneumonia associated with fluticasone propionate and budesonide COPD therapy. Compared with placebo or LABAs, we found that fluticasone p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 60 publications
1
52
2
2
Order By: Relevance
“…Differences in outcome between ICSs and placebo may be due to uneven distribution of baseline characteristics because patients with more severe disease received more intensive treatment; however, patient subgroups based on the ICS they received were well matched, such that baseline characteristics cannot explain differences between fluticasone and other ICSs 74. Fluticasone differs structurally from beclomethasone and budesonide because it has a fluorine moiety, which leads to distribution in the lipid membranes and slower clearance from lungs and other tissue, which may impact lung immunity and inflammatory responses 74,76. This study also suggested that the use of LAMA therapy may ameliorate some of the respiratory adverse effects of ICSs, supporting their use in combination 74.…”
Section: Effect Of Icss On Pneumonia Risk In Patients With Copdmentioning
confidence: 99%
“…Differences in outcome between ICSs and placebo may be due to uneven distribution of baseline characteristics because patients with more severe disease received more intensive treatment; however, patient subgroups based on the ICS they received were well matched, such that baseline characteristics cannot explain differences between fluticasone and other ICSs 74. Fluticasone differs structurally from beclomethasone and budesonide because it has a fluorine moiety, which leads to distribution in the lipid membranes and slower clearance from lungs and other tissue, which may impact lung immunity and inflammatory responses 74,76. This study also suggested that the use of LAMA therapy may ameliorate some of the respiratory adverse effects of ICSs, supporting their use in combination 74.…”
Section: Effect Of Icss On Pneumonia Risk In Patients With Copdmentioning
confidence: 99%
“…In some of these studies, there was uncertainty over the diagnosis of pneumonia because there was no radiologic confirmation, [27][28][29] but some others confirmed that ICS especially fluticasone was related with higher radiologically proven pneumonia risk in COPD patients. 30 In our study, the diagnosis of pneumonia depends on radiographic confirmation based on current pneumonia guidelines. 2 The study was not designed to test the relationship of ICS use and pneumonia risk but to test whether the ICS use had an impact on the clinical, radiologic and laboratory characteristics of CAP.…”
Section: Discussionmentioning
confidence: 97%
“…In the previous studies, the relationship between ICS use in patients with COPD and pneumonia was overwhelmingly researched. In some of these studies, there was uncertainty over the diagnosis of pneumonia because there was no radiologic confirmation, but some others confirmed that ICS especially fluticasone was related with higher radiologically proven pneumonia risk in COPD patients …”
Section: Discussionmentioning
confidence: 99%
“…Chronic bronchitis is a key pathological feature of chronic obstructive pulmonary disease (70). Clinical management of chronic bronchitis may include LABA/GCS interventions including formoterol/budesonide combination (71)(72)(73). LABA/GCS are transcriptionally active in airway epithelial cells resulting in broad anti-inflammatory activities (49).…”
Section: Discussionmentioning
confidence: 99%
“…LABA/GCS are transcriptionally active in airway epithelial cells resulting in broad anti-inflammatory activities (49). Despite their widespread use, recent analyses of LABA/GCS efficacy and mechanisms have demonstrated that these compounds may suppress antiviral immunity, which could increase susceptibility to subsequent bacterial infections (12,(71)(72)(73)(74). Importantly, the efficacy of LABA/GCS therapies may be compromised by tobacco smoke exposure (8,13), which could be contributing to the reduced efficacy in certain patient populations.…”
Section: Discussionmentioning
confidence: 99%